A re-evaluation of plasma sialic acid determination using the periodate resorcinol method versus the enzymatic method - Muniandy, S.; Qvist, R.; Zaini, A.; Chinna, K.; Ismail, I.S. (SEAMEO Regional Tropical Medicine and Public Health Network, 2005)
The concentration of plasma sialic acid was estimated using the modified chemical method and the more sensitive enzymatic method in 20 subjects with impaired glucose tolerance and 20 control subjects. The mean sialic acid concentration values of the control subjects and subjects with impaired glucose tolerance using the enzymatic method were 1.747 ± 0.047 and 2.583 ± 0.070 mmole/l and 1.753 ± 0.067 and 2.591 ± 1.02 mmole/l for the chemical method. The intra-assay coefficient of variation for the control subjects and for the subjects with impaired glucose tolerance were 1.963 and 1.583, respectively, for the enzymatic assay and 2.728 and 2.431, respectively, for the chemical assay. The inter-assay coefficient of variation for the control subjects and for the subjects with impaired glucose tolerance were 2.686 and 2.723 for the enzymatic assay, and 3.819 and 3.95 for the chemical assay. Since the values do not differ significantly, the chemical assay is a cost effective method that can be used in large epidemiological studies.